Managing Digital Interruptions from App Notifications: Implications for Digital Literacy and Student Learning Independence - Callista, Nabila Putri; Aryaningtyas, Uyuni (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2025)
In the digital era, students face great challenges in maintaining focus while studying independently due to interruptions from social media notifications. Based on cognitive load theory, repetitive distractions from notifications can strain mental capacity and hinder the learning process. Meanwhile, the self-regulated learning theory emphasizes the importance of time-management skills and controlling digital impulses, including the impact of Fear of Missing Out (FoMO) and multitasking habits. This study aims to find out the extent to which digital disruption affects students' learning independence. Using a descriptive quantitative approach, data was collected through interviews and Google Form questionnaires with non-probability sampling techniques, precisely using voluntary sampling of students of the Faculty of Tarbiyah and Teacher Training UIN K.H. Abdurrahman Wahid Pekalongan. The results showed that despite significant digital disruption, students' learning independence was relatively high, indicating their ability to adapt. This research emphasizes the importance of teaching self-management and discipline in addition to technical digital literacy to control distractions and achieve optimal learning productivity.